Low-grade malignant myofibroblastic sarcoma of the larynx: a case report - Yu Feng; Yongya Du; Maocai Li; Guotao Jia; Lili Gong; Lianqing Li (Journal of International Medical Research, 2023)
Low-grade myofibroblastic sarcoma (LGMS) is a rare malignant mesenchymal tumor derived from myofibroblasts. It is commonly identified in the head and neck, and particularly in the oral cavity, but rarely in the larynx. In this case report, we describe a patient who presented with hoarseness and underwent electronic fiber laryngoscopy, which revealed a neoplasm on the surface of his left vocal cord. The vocal cord tumor was resected under general anesthesia, and a malignant LGMS was diagnosed on postoperative pathologic examination. The results of immunohistochemical staining of the sections for vimentin (diffuse +), actin (partial +), and desmin (−) were consistent with this diagnosis. The patient recovered well after the surgery, and there was no recurrence of the neoplasm.